2020
DOI: 10.1109/access.2020.3022850
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Graph Isomorphism Network for Molecular ADMET Properties Prediction

Abstract: The evaluation of absorption, distribution, metabolism, exclusion, and toxicity (ADMET) properties plays a key role in a variety of domains including industrial chemicals, agrochemicals, cosmetics, environmental science, food chemistry, and particularly drug development. Since molecules are often intrinsically described as molecular graphs, graph neural networks have recently been studied to improve the prediction of ADMET properties. Among many graph neural networks published in recent years, Graph Isomorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Several studies have systematically analyzed the identifiability of such models 1,27,28 including our own studies, considering typical plant data collected from intensive measurement campaigns, which showed that among 60 plus model parameters, only a handful of them (6-10 parameter subsets) could be uniquely estimated from the data. These issues has been recognized already by calibration protocols in fact 29,30 . The rest of the model parameters need to be fixed or assumed when applying these models to simulate the activated sludge plants.…”
Section: Validation and Complexity Issues Of Asmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have systematically analyzed the identifiability of such models 1,27,28 including our own studies, considering typical plant data collected from intensive measurement campaigns, which showed that among 60 plus model parameters, only a handful of them (6-10 parameter subsets) could be uniquely estimated from the data. These issues has been recognized already by calibration protocols in fact 29,30 . The rest of the model parameters need to be fixed or assumed when applying these models to simulate the activated sludge plants.…”
Section: Validation and Complexity Issues Of Asmsmentioning
confidence: 98%
“…More details of these different molecular featurizations and models can be found elsewhere 29 . The graph-based featurizations and neural networks have recently gained significant research attention in cheminformatics and bioinformatics due to their superior performances on molecular ML tasks, as found in recent literature 29,30,60 . For instance, a spatial graph-based molecular representation of amino acid residue pairs has allowed AlfaFold 61 , an AI program developed by DeepMind, to perform 3D protein structure predictions far more accurately than ever made.…”
Section: Proposal Of a Solutionmentioning
confidence: 99%
“…For instance, the nonidentical molecules, decalin and 1,1-bicyclopentane (Figure S1 in the Supplementary Materials), can be recognized as the same molecule in molecular graph network due to their identical topology [34]. This issue resulted in a lower predictive power of the model [35], causing a difficulty with bioactivity prediction [36]. Accordingly, multiple aggregation strategies have been proposed to improve the GNN's performance, leading to the development of the principal neighborhood aggregation (PNA) method by DeepMind [37].…”
Section: Introductionmentioning
confidence: 99%
“…Graph convolutional neural networks (GCNNs) have shown particular promise in predicting properties of small molecules. These properties can be biological activity against protein targets (Yang et al, 2020;Sakai et al, 2021;Nguyen et al, 2020), more general pharmacokinetics and physicochemical properties (Montanari et al, 2019;Peng et al, 2020;Feinberg et al, 2020) or toxicity (Ma et al, 2020). Using accurate in silico predictions of such properties to prioritize the synthesis of compounds can lead to tremendous time and cost savings during drug discovery projects.…”
Section: Introductionmentioning
confidence: 99%